Pay for performance : evaluating performance appraisal and merit pay - Milkovich, George T.; Wigdor, Alexandra K. (National Academy Press, 1991)
Looks at performance appraisal and pay practices in the private sector and describes how private industry experience is relevant to federal pay reform. This book focuses on the needs of the federal government, exploring how the federal pay system evolved; evidence on federal employee attitudes toward their work, and their pay; and more.